"This is Not a Company; It is a Cause":Class, Gender and the Toronto Housing Company, 1912–1920 - Purdy, Sean (Urban History Review / Revue d'histoire urbaine, 1993)
Historians of public housing have recently drawn attention to the ways in which housing designs are not merely reflections of societal attitudes, but rather, form part of the dominant ideological and political agenda. This article takes its cue from these insights by exploring an early Canadian state-assisted housing venture, the Toronto Housing Company (THC). The purposes, development, layout and internal design of Riverdale Courts, the major site of the THC endeavour, evolved through the interplay of class-specific and gendered practices, revealing reformers' recognition of the desire to rectify a perceived crisis in social order. The concentration on the quality and internal ordering of workers' homes went beyond purely economic grounds: the ideological role housing could play in regulating social consent was also a pivotal concern. This early case of social reform represents one facet of the state's and the reform movement's increasing engagement with the daily lives of workers through the attempt to shape a proficient, contented and internally-divided workforce.